2D V2O5 nanosheets as a binder-free high-energy cathode for ultrafast aqueous and flexible Zn-ion batteries. (April 2020) - Javed, Muhammad Sufyan; Lei, Hang; Wang, Zilong; Liu, Bo-tian; Cai, Xiang; Mai, Wenjie
Abstract: Rechargeable aqueous Zn-ion batteries (ZIBs) are regarded as one of the most promising energy storage devices due to their intrinsic safety and the extensive stockpile of Zn. It is still challenging to prepare ultrafast flexible devices with high energy/power density and satisfactory stability. Herein, two-dimensional ultrathin vanadium pentoxide (V2 O5 ) nanosheets grown directly on titanium (Ti) substrate (V2 O5 –Ti) are prepared as a novel flexible cathode with high energy density for ultrafast aqueous and flexible ZIBs. Benefiting from the merits of exposed active sites and increased electrical conductivity, our optimized V2 O5 –Ti cathode exhibits a remarkable discharge capacity of 503.1 mAh g −1 at 100 mA g −1 and long-term stability with 86% retention after over 700 cycles at 500 mA g −1 in the aqueous coin cell. The charge storage mechanism of this V2 O5 –Ti cathode is investigated by in-situ Raman spectroscopy, ex-situ X-ray diffraction, and X-ray photoelectron spectroscopy. Remarkably, based on this flexible cathode, we designed an ultrafast and flexible quasi-solid-state zinc ion battery (f-V2 O5 –Ti//Zn), which can achieve the capacity of 377.5 mAh g −1 and energy density of 622 Wh kg −1 when charged at 4 A g −1 for less than 6 min. It also exhibits the power density of 6.4 kW kg −1 at an ultrahigh current density of 20 A g −1, which outperforms most previously reported aqueous/flexible ZIBs. As a result of superior performance, our ultrafast flexible quasi-solid-state ZIB is believed to be a promising candidate for flexible and wearable energy storage systems. Graphical abstract: Image 1 Highlights: The binder-free V2O5–Ti cathode exhibits remarkable discharge capacity and long-term stability in aqueous electrolyte. In-situ Raman spectroscopy are revealed to understand the charge storage mechanism of V2O5–Ti cathode. Flexible solid-state ZIB exhibits ultrafast charge-storage property with high capacity, energy density and stability.